Metode Drill Menggunakan Media Clay dalam Pembelajaran Huruf Hijaiah Bagi Anak Tunarungu - Najwa Azzahra, Aura Mutiara (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Learning hijaiah letters for deaf children presents unique challenges, especially in distinguishing the sounds of these letters due to hearing limitations. This study aims to describe the implementation of the drill method using clay media in teaching hijaiah letters to deaf children at PKBM. The research employs a qualitative approach with a phenomenological method. Data was collected through observations and interviews with one teacher. Data analysis was conducted through data reduction, presentation, and conclusion drawing.The study results indicate that the drill method can help enhance children's memory and understanding of hijaiah letters, primarily through repetitive exercises and visually appealing clay media. Using clay media provides a more engaging visual learning experience, improving children's concentration and involvement in the learning process. The combination of the drill method, clay media, and sign language has proven effective in helping children accurately recognize the shapes of hijaiah letters. This study highlights that the learning of hijaiah letters can be better implemented through a more interactive approach tailored to the needs of deaf children